The use of faunal evidence to reconstruct site history and Hoedjiespunt 1 (HDP1), Western Cape - Stynder, Deano Duane; Stynder, Deano Duane (Department of Archaeology, 2017)
Hoedjiespunt 1 (HDP 1 ), is one of few later Middle Pleistocene to earlier Late Pleistocene African sites to yield well provenanced MSA hominid fossils, lending special significance to this site. The vertebrate fauna from this location, which consists of a palaeontological and an archaeological site, is described and analysed using both the taphonomic and controlled comparison approaches. The information obtained via this study allows for a better understanding of the context in which and the conditions under which these two sites were formed. Stratigraphic evidence and spatial information, suggest that the bones in the palaeontological site were in all likelihood accumulated in a cavity, thus postdating the sediments in which they occur. Circumstantial evidence, in addition to Klein and Cruz-Uribe's (1984) criteria for distinguishing assemblages accumulated by hyaenas from those accumulated by people, points towards the brown hyaena as the most likely accumulator of this assemblage. It is also suspected that the bone in the archaeological assemblage, may postdate the sediments in which they occur. This is suggested by the presence at the site, of tools manufactured out of calcrete, similar to the calcrete carapace which caps the stratigraphic sequence. Although density mediated destruction seems to have been the major cause of discrepancies in skeletal part abundance in the palaeontological site, it was found not to have been severe. The composition of species represented in the two assemblages differ. It was found that, apart from containing a small percentage of marine animals, the palaeontological site is dominated by grazing ungulates and carnivores. This assemblage was accumulated during a period of lowered sea level, or "glacial". On the other hand, the sample from the archaeological site contains proportionally fewer ungulates and carnivores, more small animals and more marine animals, reflecting a period of marine transgression, or "interglacial".